Auxiliary brazing method for multi-scale microstructure on surface of laser-induced composite material

By induced laser-induced multi-scale microtexture assisted brazing on the surface of composite materials, mechanical interlocking pinned structures and low linear expansion coefficient particles are formed, which solves the problem that the brazed joints of fiber-reinforced ceramic matrix composite materials are prone to break under harsh working conditions, and improves the mechanical properties and toughness of the joints.

CN119703248AActive Publication Date: 2025-03-28JIANGSU UNIV

Patent Information

Application Number
CN202510005463.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-02
Publication Date
2025-03-28
Estimated Expiration
2045-01-02

AI Technical Summary

Technical Problem

Fiber-reinforced ceramic matrix composite materials and metal brazed joints are prone to rapid brittle fracture failure under harsh working conditions such as high temperature, thermal vibration, alternating load load-bearing, and there are high residual stresses in the brazed joints, which weakens the joint load-bearing capacity.

Method used

By induced laser-induced multi-scale microtexture assisted brazing on the surface of composite materials, a mechanical interlocking pinning structure is formed, and low linear expansion coefficient particles are formed on the surface of fiber-reinforced ceramic matrix composite materials to achieve brazing joint recombination and alleviate residual stress of joints.

Benefits of technology

It improves the mechanical properties and toughness of the brazed joint, relieves the residual stress of the joint, and enhances the service reliability of the joint.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119703248A_ABST
    Figure CN119703248A_ABST
Patent Text Reader

Abstract

The invention provides a laser-induced composite material surface multi-scale micro-texture assisted brazing method which comprises the following steps: step 3, carrying out surface texturing treatment on a to-be-welded surface of a fiber reinforced ceramic matrix composite obtained in step 2 by using a laser in air, and in the laser texturing process, carrying out surface texturing treatment on the to-be-welded surface of the fiber reinforced ceramic matrix composite, the fiber-reinforced ceramic matrix composite material is placed in the center of a laser objective table, then laser with the defocusing amount being-5-5 mm, the laser power being 0-300 W and the laser scanning speed being 5-100 mm s <-1 > is adopted for vertical irradiation, and the textured fiber-reinforced ceramic matrix composite material is obtained; and fourthly, active brazing filler metal is placed between the textured fiber-reinforced ceramic matrix composite obtained in the third step and the to-be-welded face of metal, and brazing assembly is completed. According to the method, the original straight interface reaction layer is textured through a surface material reduction method, and compared with a surface material increase method which is complex in process, harsh in process condition and high in process cost, the economic cost and the labor cost of the process are greatly reduced through the method.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of fiber-reinforced ceramic-based composite materials, and in particular to a method for laser-induced composite material surface multi-scale micro-texture assisted brazing. Background Art

[0002] Fiber-reinforced ceramic matrix composites are widely used in high-end fields such as aerospace, high-speed transportation, and nuclear energy due to their excellent high temperature resistance, low density, high strength, high modulus, and high toughness. These materials usually need to be connected by vacuum brazing technology to ensure reliability and durability in extreme environments. Vacuum brazing not only provides precise dimensional control and surface quality, but also can simultaneously complete the brazing and quenching processes to improve production efficiency. It is a key technology for manufacturing high-performance composite components. However, fiber-reinforced ceramic matrix composite components often serve under harsh working conditions such as high temperature, thermal vibration, and alternating loads, which makes the brazed joint interface prone to rapid brittle fracture failure. In this regard, it is urgent to improve the toughness of the weld while slowly releasing the high residual stress of the joint to ensure the service reliability of the joint under working conditions.

[0003] Current research generally believes that the interface reaction layer between fiber-reinforced ceramic matrix composites and brazing seams in fiber-reinforced ceramic matrix composite-metal brazing joints is the biggest hidden danger of joint fracture. In this regard, researchers mainly use two methods to improve the brazing connection performance of the joint: brazing seam compositeization and interface structure modification. Among them, brazing seam compositeization mainly improves the thermophysical properties and plastic toughness of the weld by introducing a high-performance reinforcement phase that is as evenly distributed as possible into the brazing seam, thereby achieving joint strengthening. Admittedly, this method can effectively form a gradient transition of joint properties and indirectly improve the failure threshold of the interface between ceramic and brazing seams, but it cannot change the nature of the rapid expansion of dislocations in the flat interface structure during the joint integration process, which limits the further improvement of joint strength and toughness. In contrast, the method of interface structure modification can roughen the originally flat interface reaction layer by surface additive or subtractive methods, thereby directly intervening in the interface fracture behavior between ceramics or composite materials and brazing seams. However, the surface additive method has the problems of complex process, harsh process conditions and high process cost. Summary of the invention

[0004] The purpose of the present invention is to provide a method for laser-induced multi-scale micro-texture assisted brazing of composite material surfaces, which solves the problem that due to the strong mismatch in thermal expansion coefficient and elastic modulus between fiber-reinforced ceramic-based composite materials and metal materials, high residual stress exists in the brazed joint, which weakens the bearing capacity of the joint. At the same time, the attitude control engine of aerospace vehicle mainly serves under harsh working conditions of high temperature, thermal vibration and alternating load coupling, which leads to the problem that the interface of the transition ring-nozzle heterogeneous brazed joint is prone to rapid brittle fracture failure.

[0005] In order to achieve the above-mentioned object of the invention, a method for laser-induced multi-scale micro-texture assisted brazing of composite material surface comprises the following steps:

[0006] Step 1: The fiber-reinforced ceramic matrix composite material is cut by wire cutting to obtain a block of any required size, and then ultrasonically cleaned in ethanol for 10 to 15 minutes and dried in an oven;

[0007] Step 2: The clean fiber-reinforced ceramic matrix composite material to be welded obtained in step 1 is polished with 600-800 mesh silicon carbide sandpaper to remove scratches on the fiber-reinforced ceramic matrix composite material to be welded, and then ultrasonically cleaned in ethanol for 10-15 minutes, and placed in an oven at 60-80° C. to dry for use;

[0008] Step 3: Use a laser to perform surface texturing on the fiber-reinforced ceramic matrix composite material to be welded obtained in step 2 in the air. During the laser texturing process, the fiber-reinforced ceramic matrix composite material is placed at the center of the laser objective stage, and then the defocus is -5 to 5 mm, the laser power is 0 to 300 W, and the laser scanning speed is 5 to 100 mm s –1 The textured fiber-reinforced ceramic matrix composite material is obtained by vertical laser irradiation.

[0009] Step 4: placing an active brazing filler metal between the textured fiber-reinforced ceramic matrix composite material obtained in step 3 and the metal surface to be welded to complete the brazing assembly;

[0010] Step 5: Place the welded assembly from step 4 into a vacuum brazing furnace and evacuate until the vacuum degree is less than 3×10 –3 Pa, then 5~30℃min –1 The vacuum brazing furnace is heated to 30-120℃ above the melting point of the brazing material at a heating rate, then kept warm for 5-60min, and finally heated at 1-10℃min. –1 The vacuum brazing furnace is cooled to room temperature at a cooling rate to complete the brazing process and obtain fiber-reinforced ceramic matrix composite materials or ceramic and metal brazing joints.

[0011] Compared with the prior art, the present invention has the following beneficial effects:

[0012] 1. The present invention utilizes laser irradiation to obtain a fiber-reinforced ceramic matrix composite material with a significant precision reduction effect and a fiber array serrated structure textured fiber-reinforced ceramic matrix composite material, which realizes the modification of the interface microstructure of the parent material, thereby forming a mechanical interlocking pinning structure in the brazed joint; at the same time, low linear expansion coefficient particles are formed on the surface of the fiber-reinforced ceramic matrix composite material, which realizes brazing joint compounding, improves brazing joint performance, and relieves joint residual stress; the alternating structure formed by the high-strength and tough fiber-reinforced ceramic matrix composite material matrix and the excellent plastic brazing material solidified in the reduction zone can fully consume the energy of crack expansion by inducing crack bridging, crack deflection and fiber pulling out when bearing external force, thereby improving the mechanical properties of the joint. At the same time, the uniform and fine high-performance strengthening phase produced by laser-induced surface texturing of fiber-reinforced ceramic matrix composite materials can effectively improve the thermophysical properties and plastic toughness of the weld, thereby achieving joint strengthening.

[0013] 2. The present invention roughens the originally straight interface reaction layer by means of surface subtraction. Compared with the surface additive method with complex process, harsh process conditions and high process cost, this method greatly reduces the economic cost and labor cost of the process. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 A schematic diagram of the overall structure of a method for laser-induced multi-scale micro-texture assisted brazing of a composite material surface provided by the present invention;

[0015] Figure 2 A schematic diagram of the partial structure of a method for laser-induced multi-scale micro-texture assisted brazing of a composite material surface provided by the present invention. DETAILED DESCRIPTION

[0016] To make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be described clearly and completely in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them.

[0017] Embodiment 1

[0018] A method for laser-induced multi-scale microtexture-assisted brazing of composite material surface comprises the following steps:

[0019] 1. C f / SiC composites were cut by wire cutting to obtain blocks of 5 mm × 5 mm × 5 mm, then ultrasonically cleaned in ethanol for 10 min and dried in an oven;

[0020] 2. The clean C obtained in step 1 f The surface to be welded of the SiC composite material was polished with 800-grit silicon carbide sandpaper to remove the C f / SiC composite material to be welded, and then ultrasonically cleaned in ethanol for 10 min, and placed in an oven at 80 °C for drying before use;

[0021] 3. Use continuous laser to irradiate the C obtained in step 2 in air. f The surface of the SiC composite material to be welded is subjected to surface texturing. During the laser texturing process, C f The / SiC composite material was placed at the center of the laser objective stage, and then the defocus was 0 mm, the laser power was 80 W, and the laser scanning speed was 50 mm s –1 The laser is irradiated vertically to obtain the textured C f / SiC composite materials;

[0022] 4. Place the Ag-27.5Cu-4.5Ti (wt.%) active solder foil on the textured C f The brazing assembly is completed between the surface to be welded of the SiC composite material and the metal Nb;

[0023] 5. Place the welded assembly from step 4 into a vacuum brazing furnace and evacuate until the vacuum degree is less than 3×10 –3 Pa, then 10℃min –1 The vacuum brazing furnace was heated to 880℃ at a heating rate and then kept warm for 10min. –1 The vacuum brazing furnace is cooled to room temperature at a cooling rate to complete the brazing process and obtain C f / SiC composite material and metal Nb brazing joint.

[0024] Embodiment 2

[0025] The difference between this embodiment and the first embodiment is that: in step 1, C f The SiC / SiC composite material was cut into a block of 10 mm×10 mm×8 mm by wire cutting, and then ultrasonically cleaned in ethanol for 15 min and dried in an oven. The other steps and parameters were the same as those in Example 1.

[0026] Embodiment 3

[0027] The difference between this embodiment and the first and second embodiments is that: in step 2, the clean fiber-reinforced ceramic matrix composite material to be welded is polished with 800-mesh silicon carbide sandpaper to remove scratches on the fiber-reinforced ceramic matrix composite material to be welded, and then ultrasonically cleaned in ethanol for 10 minutes, and placed in an oven at 60°C for drying before use. The other steps and parameters are the same as those in the first and second embodiments.

[0028] Embodiment 4

[0029] The difference between this embodiment and embodiments one to three is that: in step two, the clean fiber-reinforced ceramic-based composite material surface to be welded is polished with 600-mesh silicon carbide sandpaper to remove scratches on the fiber-reinforced ceramic-based composite material surface to be welded, and then ultrasonically cleaned in ethanol for 15 minutes, and placed in an oven at 80°C for drying before use. The other steps and parameters are the same as those of embodiments one to three.

[0030] Embodiment 5

[0031] The difference between this embodiment and embodiments 1 to 4 is that: in step 3, the defocusing amount is 0 mm, the laser power is 80 W, and the laser scanning speed is 50 mm s -1 The laser is vertically irradiated to obtain a textured fiber-reinforced ceramic matrix composite material. The other steps and parameters are the same as those in Examples 1 to 4.

[0032] Embodiment 6

[0033] The difference between this embodiment and embodiments 1 to 5 is that: in step 3, the defocusing amount is -1 mm, the laser power is 40 W, and the laser scanning speed is 80 mm s -1 The laser is vertically irradiated to obtain a textured fiber-reinforced ceramic matrix composite material. The other steps and parameters are the same as those in Examples 1 to 5.

[0034] Embodiment 7

[0035] The difference between this embodiment and embodiments 1 to 6 is that: in step 3, the defocusing amount is 1 mm, the laser power is 120 W, and the laser scanning speed is 30 mm s -1 The laser is vertically irradiated to obtain a textured fiber-reinforced ceramic matrix composite material. Other steps and parameters are the same as those of Examples 1 to 6.

[0036] Embodiment 8

[0037] The difference between this embodiment and embodiments 1 to 7 is that the solder in step 4 is an active solder such as Ag-based, Cu-based, Ti-based, Ni-based, etc. The other steps and parameters are the same as those of embodiments 1 to 7.

[0038] Embodiment 9

[0039] The difference between this embodiment and embodiments 1 to 8 is that: in step 4, the fiber-reinforced ceramic matrix composite material is C f / SiC composite materials, C f / C composite material or C f -C / SiC composite material, etc. Other steps and parameters are the same as those of Examples 1 to 8.

[0040] Embodiment 10

[0041] The difference between this embodiment and embodiments 1 to 9 is that the metal matrix in step 3 is metal Nb, Ni-based high temperature alloy, TC4 titanium alloy, TiAl alloy, etc. The other steps and parameters are the same as those in embodiments 1 to 9.

[0042] like Figure 1 As shown, Figure 1 To use low power (80W) continuous laser to C f After surface texturing treatment of the SiC surface, the C f A multi-scale hierarchical structure appears on the surface of the SiC / SiC composite material, namely the height difference between the planar fiber area and the normal fiber area, and the height difference between the fiber and the matrix material. At the same time, only the matrix material is observed to be selectively removed, and the carbon fibers are retained.

[0043] The C f The morphology of the joints brazed by 80W laser textured C f / SiC-Nb joints show continuous hierarchical pinning and a complete connection interface with non-straight structure. f The reaction layer interface on the / SiC side is replaced by a fiber-reinforced transition zone.

[0044] like Figure 2 As shown, compared with the direct brazing joint, the C f The room temperature shear strength of the / SiC-Nb joint increased by 1 times to ~46MPa.

[0045] The present invention utilizes laser irradiation to obtain a fiber-reinforced ceramic matrix composite material with a significant precision reduction effect and a fiber array serrated structure textured fiber-reinforced ceramic matrix composite material, which realizes the modification of the interface microstructure of the parent material, thereby forming a mechanical interlocking pinning structure in the brazed joint; at the same time, low linear expansion coefficient particles are formed on the surface of the fiber-reinforced ceramic matrix composite material, which realizes brazing joint compounding, improves brazing joint performance, and relieves joint residual stress; the alternating structure formed by the high-strength and tough fiber-reinforced ceramic matrix composite material matrix and the excellent plastic brazing material solidified in the reduction zone can fully consume the energy of crack expansion by inducing crack bridging, crack deflection and fiber pulling out when bearing external force, thereby improving the mechanical properties of the joint. At the same time, the uniform and fine high-performance strengthening phase produced by the laser-induced surface texturing of the fiber-reinforced ceramic matrix composite material can effectively improve the thermophysical properties and plastic toughness of the weld, thereby achieving joint strengthening.

[0046] The present invention roughens the originally straight interface reaction layer by using a surface subtractive method. Compared with a surface additive method with complex process, harsh process conditions and high process cost, this method greatly reduces the economic cost and labor cost of the process.

[0047] The above embodiments are only used to illustrate the present invention and are not intended to limit the technical solutions described in the present invention. Although the present invention has been described in detail with reference to the above embodiments, the present invention is not limited to the above embodiments. Therefore, any modification or equivalent replacement of the present invention; and all technical solutions and improvements thereof that do not depart from the spirit and scope of the invention are included in the scope of the claims of the present invention.

Claims

1. A method for laser-induced multi-scale microtexture assisted brazing of composite materials, characterized in that: The following steps are involved: Step 1: The fiber-reinforced ceramic matrix composite material is cut by wire cutting to obtain a block of any required size, and then ultrasonically cleaned in ethanol for 10 to 15 minutes and dried in an oven; Step 2: The clean fiber-reinforced ceramic matrix composite material to be welded obtained in step 1 is polished with 600-800 mesh silicon carbide sandpaper to remove scratches on the fiber-reinforced ceramic matrix composite material to be welded, and then ultrasonically cleaned in ethanol for 5-15 minutes, and placed in an oven at 60-80° C. to dry for use; Step 3: Use a laser to perform surface texturing on the fiber-reinforced ceramic matrix composite material to be welded obtained in step 2 in the air. During the laser texturing process, the fiber-reinforced ceramic matrix composite material is placed at the center of the laser objective stage, and then the defocus is -5 to 5 mm, the laser power is 0 to 300 W, and the laser scanning speed is 5 to 100 mm s –1 The textured fiber-reinforced ceramic matrix composite material is obtained by vertical laser irradiation. Step 4: placing an active brazing filler metal between the textured fiber-reinforced ceramic matrix composite material obtained in step 3 and the metal surface to be welded to complete the brazing assembly; Step 5: Place the welded assembly from step 4 into a vacuum brazing furnace and evacuate until the vacuum degree is less than 3×10 –3 Pa, then 5~30℃min –1 The vacuum brazing furnace is heated to 30-120℃ above the melting point of the brazing material at a heating rate, then kept warm for 5-60min, and finally heated at 1-10℃min. –1 The vacuum brazing furnace is cooled to room temperature at a cooling rate to complete the brazing process and obtain fiber-reinforced ceramic matrix composite materials or ceramic and metal brazing joints.

2. The method for laser-induced composite material surface multi-scale microtexture assisted brazing according to claim 1, characterized in that: In step 1, the fiber-reinforced ceramic matrix composite material is cut by wire cutting to obtain a block with a size of 5 mm×5 mm×5 mm, which is then ultrasonically cleaned in ethanol for 10 minutes and dried in an oven for later use.

3. The method for laser-induced composite material surface multi-scale microtexture assisted brazing according to claim 2, characterized in that: During the laser texturing process in step 3, C f The SiC fiber-reinforced ceramic matrix composite material was placed at the center of the laser objective stage, and then the defocus was 0 mm, the laser power was 80 W, and the laser scanning speed was 50 mm s –1 The laser is irradiated vertically to obtain the textured C f / SiC fiber reinforced ceramic matrix composites.

4. The method for laser-induced composite material surface multi-scale microtexture assisted brazing according to claim 2, characterized in that: During the laser texturing process in step 3, C f The SiC fiber-reinforced ceramic matrix composite material was placed at the center of the laser objective stage, and then the defocus was –1 mm, the laser power was 40 W, and the laser scanning speed was 10 mm s –1 The laser is irradiated vertically to obtain the textured C f / SiC fiber reinforced ceramic matrix composites.

5. The method for laser-induced composite material surface multi-scale microtexture assisted brazing according to claim 2, characterized in that: During the laser texturing process in step 3, C f The C fiber-reinforced ceramic matrix composite material was placed at the center of the laser objective stage, and then the defocus was –1 mm, the laser power was 120 W, and the laser scanning speed was 80 mm s –1 The laser is irradiated vertically to obtain the textured C f / C fiber reinforced ceramic matrix composites.

6. The method for laser-induced composite material surface multi-scale microtexture assisted brazing according to claim 2, characterized in that: During the laser texturing process in step 3, C f The C-SiC fiber-reinforced ceramic matrix composite material was placed at the center of the laser objective stage, and then the defocus was 1 mm, the laser power was 160 W, and the laser scanning speed was 30 mm s –1 The laser is irradiated vertically to obtain the textured C f / C-SiC fiber reinforced ceramic matrix composites.

7. The method for laser-induced composite material surface multi-scale microtexture assisted brazing according to claim 2, characterized in that: In step 4, the textured C f / C composite material and metal GH3536, heating rate 15℃min –1 The brazing temperature is 1050℃, the temperature is kept for 5min, and the cooling rate is 3℃min –1 .

8. The method for laser-induced composite material surface multi-scale microtexture assisted brazing according to claim 2, characterized in that: In step 4, Ag-27.5Cu-4.5Ti (wt.%) active solder is used as solder to solder the textured C f / SiC composite material and metal Nb, heating rate 10℃min –1 The brazing temperature is 880℃, the temperature is kept for 10min, and the cooling rate is 5℃min –1 .

Citation Information

Patent Citations

  • Method for brazing fiber reinforced composite material and metal under assistance of selective hot corrosion

    CN112548253A

  • Method for assisting brazing of fiber reinforced composite material or ceramic and metal through hollow net-shaped flexible carbon sponge transition layer

    CN116727793A

  • Method for strengthening ceramic or ceramic-based composite material and metal brazing through bionic structure interface

    CN117399734A

  • Method for obtaining high-resistance brazed joints of multiple-layer composite materials of ceramic / ceramic and metal / ceramic type, and multiple-layer composite materials obtained through the said method

    EP1500455A1

  • Method for strengthening joining performance of ceramic material by means of texturing

    WO2021196004A1

Cited By

  • Brazing connection method for carbon / carbon composite material and high-temperature alloy

    CN120816081A

  • Ceramic / metal heterogeneous material connection method based on thermal-shape cooperative regulation and control

    CN121798076A